2013
DOI: 10.1186/1471-2458-13-1240
|View full text |Cite
|
Sign up to set email alerts
|

Causes of discomfort in the academic workplace and their associations with the different burnout types: a mixed-methodology study

Abstract: BackgroundBurnout is the result of prolonged workplace exposure to chronic stress factors and may present itself in one of the following subtypes: “frenetic”, “under-challenged” and “worn-out”. The aims of the present study were to identify the causes of workplace discomfort that affect employees in large organizations and to determine the predictive power of these causes with regard to the burnout subtypes.MethodWe employed a qualitative and quantitative analysis (QQA), using a cross-sectional design with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…As evidenced by several investigations conducted in different work environments, our study with journalists showed that the higher the manageable load index, the lower the level of EE [ 9 , 31 ]. However, the possibility of exercising “control” over the task itself was not shown to be an explanatory variable for any of the burnout dimensions, as we hypothesized before this study began.…”
Section: Discussionmentioning
confidence: 73%
“…As evidenced by several investigations conducted in different work environments, our study with journalists showed that the higher the manageable load index, the lower the level of EE [ 9 , 31 ]. However, the possibility of exercising “control” over the task itself was not shown to be an explanatory variable for any of the burnout dimensions, as we hypothesized before this study began.…”
Section: Discussionmentioning
confidence: 73%
“…Venting of emotions also presented significant bivariate relationships with all of the subscales belonging to the different burnout subtypes. This coping strategy could be a general feature of burnout, although the specific content presented in the complaints could be different depending on the type of burnout experiences, as has recently been reported [50]. Consequently, the frenetic subtype would complain about the organizational hierarchy, which imposes limits to his or her high ambition; the underchallenged subtype would express distress about the routine nature of his or her obligations, which would hinder personal development; and the worn-out subtype would be annoyed by the monitoring systems, owing to his or her negligent behaviour.…”
Section: Discussionmentioning
confidence: 76%
“…In general, under-challenged workers are disenchanted and feel trapped in an occupational activity that produces no gratifications and lack of personal growth [55]. Therefore, one might suppose that those older Brazilian PC providers that could be highly dependent on their salary and thus were obliged to carry on certain routine duties that maybe did not satisfy them and, at the same time, were not able to follow possible desires to change their job, could be suffering from the under-challenged subtype [91].…”
Section: Sociodemographic Related To the Subtypesmentioning
confidence: 99%